A Systematic Policy Review of Black Maternal Health-Related Policies Proposed Federally and in Massachusetts: 2010–2020 - Carvalho, Keri; Kheyfets, Anna; Maleki, Pegah; Miller, Brenna; Abouhala, Siwaar; Anwar, Eimaan; Amutah-Onukagha, Ndidiamaka (Frontiers in Public Health, 2021)
Background Black women in the United States experience maternal mortality three to four times more often than white women (Chinn et al., 2020; Creanga et al., 2014). States vary in degree of disparity, partially due to programs and policies available to pregnant people. In Massachusetts, Black women were approximately twice as likely as white women to experience pregnancy-associated mortality, with a large percentage of these deaths reported to be preventable (Massachusetts Department of Health, 2014). Methods Using Massachusetts as a state-level comparison to national policies, we searched the US Congress and Massachusetts legislative databases for maternal health policies from 2010-2020. We screened 1,421 national and 360 Massachusetts bills, following set inclusion/exclusion criteria. Data analysis included 1) assessment of bill characteristics, 2) thematic analysis, and a 3) quality appraisal following an adapted model of the analytical framework for evaluating public health policy proposed by the National Collaborating Centre for Healthy Public Policy. Additionally, our data analysis identified the level of racism (internalized, interpersonal or institutional) that each policy addressed. Results From 2010 to 2020, 31 national and 16 state-level policies were proposed that address maternal health and racial disparities. The majority of policies addressed racism at the institutional level alone (National: N=19, 61.3%; Massachusetts: N=14, 87.5%). Two national and two Massachusetts-level policies became law, while two national policies passed only the House of Representatives. Our critical appraisal revealed that the majority of unintended effects would be neutral or positive, however, some potential negative unintended effects were identified. The appraisal also identified 54.8% (n=17) of national policies and 68.8% (n=11) of Massachusetts with positive impact on health equity. Conclusions There has been an increase in policies proposed addressing racial disparities and health equity in maternal health over the last ten years. Although half of national policies proposed showed positive impact on health equity, shedding light on the work the U.S. is doing on a federal level to confront the Black maternal health crisis, only two policies made it to law, only one of which addressed racial disparities directly and had a positive impact on health equity.